Revitalization of Qur’anic Values in Islamic Education (Study of Surah Al-‘Alaq Verses 1–5) - Sugiarto, Fitrah; Ahlan (Universitas Pendidikan Ganesha, 2025)
Islamic education in Indonesia has experienced significant progress in line with the rapid development of technology; however, this progress is also part of Western globalization strategies to disseminate their cultural values. To overcome the negative impacts of globalization and value shifts, revitalizing Qur’anic values in Islamic education is an essential step to safeguard its existence. This article aims to construct a new perspective on the role of Islamic education in shaping students’ character, morals, and achievements to support the education of future Muslim generations through the exploration of Qur’anic values in Surah Al-‘Alaq verses 1–5. This study employs a qualitative method, specifically library research. A phenomenological approach is used to gain in-depth understanding, provide detailed descriptions, apply deep reduction, highlight intersubjectivity, and explore the meaning of the studied object. The findings indicate that the verses of Surah Al-‘Alaq (verses 1–5) contain fundamental values that can serve as guidance in the implementation of Islamic education, including submission and respect, the importance of knowledge and appreciation of science, independence and responsibility, as well as respect for the learning process.